2005
DOI: 10.1262/jrd.17031
|View full text |Cite
|
Sign up to set email alerts
|

Neural Encoding of Olfactory Recognition Memory

Abstract: Abstract. Our work with both sheep and mouse models has revealed many of the neural substrates and signalling pathways involved in olfactory recognition memory in the main olfactory system. A distributed neural system is required for initial memory formation and its short-term retention-the olfactory bulb, piriform and entorhinal cortices and hippocampus. Following memory consolidation, after 8 h or so, only the olfactory bulb and piriform cortex appear to be important for effective recall. Similarly, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 74 publications
8
66
0
Order By: Relevance
“…DA has been shown to be involved in social learning, as studies in mice have found that dopamine acting on the D1 but not the D2 dopamine receptor mediates the STFP (Choleris et al, in preparation). Mesocorticolimbic DA projections innervate many of the areas known to be involved in the STFP, such as the hippocampal region, the orbitofrontal cortex, and the amygdala (eg Bunsey and Eichenbaum, 1995;Alvarez et al, 2001;Sánchez-Andrade et al, 2005;Ross et al, 2005;Wang et al, 2007). The dopaminergic system is modulated by estrogens, both through increasing the release of DA (McDermott et al, 1994;Liu and Xie, 2004) and through decreasing the expression and activity of the DA transporter, which eliminates DA from the extracellular space (Karakaya et al, 2007).…”
Section: Effects Of Way-200070mentioning
confidence: 99%
See 2 more Smart Citations
“…DA has been shown to be involved in social learning, as studies in mice have found that dopamine acting on the D1 but not the D2 dopamine receptor mediates the STFP (Choleris et al, in preparation). Mesocorticolimbic DA projections innervate many of the areas known to be involved in the STFP, such as the hippocampal region, the orbitofrontal cortex, and the amygdala (eg Bunsey and Eichenbaum, 1995;Alvarez et al, 2001;Sánchez-Andrade et al, 2005;Ross et al, 2005;Wang et al, 2007). The dopaminergic system is modulated by estrogens, both through increasing the release of DA (McDermott et al, 1994;Liu and Xie, 2004) and through decreasing the expression and activity of the DA transporter, which eliminates DA from the extracellular space (Karakaya et al, 2007).…”
Section: Effects Of Way-200070mentioning
confidence: 99%
“…It was recently shown that the estrous cycle can affect the memory of an STFP (as reported in Sánchez-Andrade et al, 2005). When tested 24 h after interacting with a demonstrator, only mice in proestrus showed a socially acquired preference (Sánchez-Andrade et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While during lamb memory formation, extensive immediately early genes activation was found throughout the olfactory processing network, it appears that only few brain structures are engaged in retrieval of lamb memory once consolidated. During the early stages of memory consolidation, piriform and entorhinal cortices show significant expression of activation markers, while retrieval of more consolidated memory (7 days postpartum) leads to an enhanced activation of frontal and orbitofrontal cortices (Keller et al, 2004a(Keller et al, ,b, 2005Sanchez-Andrade et al, 2005). Thus, consolidation processes induce time-dependent reorganization in the network engaged in lamb recognition.…”
Section: Neural Structures and Neurochemical Processesmentioning
confidence: 99%
“…The food preference is subsequently measured in a choice test for consumption of the novel flavored food that the demonstrator ate versus a second, completely novel flavored food. Originally developed as a memory task [23,54], STFP may be used without a temporal delay between the interaction session and the choice session, to measure aspects of social communication between conspecifics [39,53]. Successful development of the food preference requires the subject mouse to interact with, and gather relevant olfactory and taste cues from, a conspecific.…”
Section: Introductionmentioning
confidence: 99%